Sistem Monitoring of Heart Rate and Blood Oxygen Automatic Oximeter+ berbasis Internet of Things (IOT) - Dewi, Sita; Zahroh, Fina Azkiyati; Firdaus, Firdaus (Universitas Hamzanwadi, 2023)
The purpose of this study was to determine the characteristics of the Automatic Oximeter+, the effect of gender, age, activity, and distance in using the Automatic Oximeter+. In general, the use of oximeters in the community is still minimal, and their knowledge of oximeters is also minimal. While the oximeter tool circulating in the community is still common and checking heart rate and oxygen saturation is still done manually. To overcome this problem, the researchers created a tool using the MAX30100 sensor to measure heart rate and oxygen saturation, and used the Bluetooth HC-05 module to send the measured values to a smartphone. The method used in this study uses repeated experiments. The data obtained will be processed using the method by calculating the validity of the tool and using simple linear regression, to determine the effect between variables. It can be concluded that this Automatic Oximeter+ has a validity value for oxygen saturation of ±98% and for heart rate of ±95%. The distance limit between the Automatic Oximeter+ and the smartphone is ± 30 m in limited space. According to research, oxygen saturation is not affected by gender, age, and activity. However, heart rate is influenced by gender, age, and activity.